MPLOYMENT AND UNDEREMPLOYMENT IN LIBYA - Wedley, William C. (Dirasat in Economics and Business, 1966)
At any given time, the resources and skills available to a country place some type of ceiling on the number of development projects which can be undertaken. Capital is needed to provide the private and social overhead investments which increase or aid the productive capabilities of the society. Inputs of natural resources are necessary so that consumption and investment goods can be produced. Foreign exchange is re quired if an insufficiency in the domestic supply of natural resources, goods, and capital necessitates a supplementation from external sources. Labor, with the correct skills and attitudes, is needed so as to combine the productive factors and to operate in the economic system. Finally, im- provements in the effectiveness of this economic system are achieved by advancements in technology and by betterment of educational standards. One of the major features of development planning is to identify those resources or skills which are limiting the potentialities for growth. With such knowledge, positive steps can be taken to alleviate the bottle- neck. At any given time, the resources and skills available to a country place some type of ceiling on the number of development projects which can be undertaken. Capital is needed to provide the private and social overhead investments which increase or aid the productive capabilities of the society. Inputs of natural resources are necessary so that consump-tion and investment goods can be produced. Foreign exchange is re- quired if an insufficiency in the domestic supply of natural resources, goods, and capital necessitates a supplementation from external sources. Labor, with the correct skills and attitudes, is needed so as to combine the productive factors and to operate in the economic system. Finally, improvements in the effectiveness of this economic system are achieved by advancements in technology and by betterment of educational stan-dards. One of the major features of development planning is to identifythose resources or skills which are limiting the potentialities for growth.With such knowledge, positive steps can be taken to alleviate the bottle-neck.